Comparison of adequate relief with symptom, global, and responder endpoints in linaclotide phase 3 trials in IBS‐C. Issue 1 (1st February 2015) - Camilleri, Michael; Lembo, Anthony J; Lavins, Bernard J; MacDougall, James E; Carson, Robyn T; Williams, Valerie SL; Nelson, Lauren M; Shiff, Steven J; Currie, Mark G; Kurtz, Caroline B; Johnston, Jeffrey M
Abstract : Background: Optimal clinical trial endpoints for irritable bowel syndrome with constipation (IBS‐C) are uncertain. Objective: The objective of this article is to compare adequate relief (AR) to abdominal/bowel symptoms, global endpoints, and FDA and EMA responder criteria; and to use AR as an anchor to assess clinically meaningful change (CMC) in IBS‐C symptoms. Methods: Using pooled 12‐week data from two phase 3 linaclotide clinical trials, daily abdominal/bowel symptoms and weekly global assessments were correlated with AR. Symptom CMC thresholds were estimated using AR as an anchor. Agreement between AR and FDA/EMA responder criteria was assessed. Results: Correlations of AR with percentage change in abdominal symptoms, bowel symptoms, and global endpoints ranged from 0.48–0.54, 0.32–0.39, and 0.61–0.71, respectively. Using AR as an anchor, CMC thresholds were 29% improvement in abdominal pain, 29% improvement in abdominal discomfort, and 0.7/week increase in CSBMs, similar to thresholds for IBS‐C responder endpoints recommended by the FDA and EMA. There was considerable agreement of weekly responder rates between AR and the FDA and EMA endpoints (on average, 70%–76% and 71%–82% of weeks with agreement, respectively). Conclusions: AR bridges IBS‐C clinical trials, putting into perspective the disparate primary endpoints recommended by professional societies and regulatory authorities, and allowing researchers, practitioners, and regulators to compare trial results.